Positive electrode material and preparation method thereof, positive electrode plate and secondary battery

By controlling the number proportion of particles below 1 μm and the conductivity of the pole piece in the ternary cathode material, the problem of structural collapse and cycle life of the material during the charge and discharge process is solved, and a cathode material with high efficiency and long life is realized.

CN119361685AActive Publication Date: 2025-01-24SHENZHEN CITY BATTERY NANOMETER TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411940456.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-01-24
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

Commercial ternary cathode materials are prone to structural collapse during charging and discharging, resulting in intergranular cracks, affecting the cycle life of the cathode materials.

Method used

Provide a cathode material, in which in the image under the 3k magnification of the scanning electron microscope, the number ratio R of particles below 1 μm satisfies 8% ≤ R ≤ 20%, and has an electrode conductivity T > 0.025S under the condition of 25MPa /cm. The material uses specific preparation methods, including atomization pyrolysis of oxide precursors and multi-temperature stage sintering, to control the number and distribution of microparticles.

Benefits of technology

The positive material has good conductive performance, reduces the battery resistance and power consumption, and improves the efficiency of energy transmission. At the same time, by controlling the proportion of the number of particles, the material has high -voltage density and high -material activity, which improves safety and circulation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361685A_ABST
    Figure CN119361685A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material and a preparation method thereof, a positive electrode plate and a secondary battery. In the positive electrode material, the number ratio R of particles with the particle size of less than 1 [mu] m is more than or equal to 8% and less than or equal to 20%; and under the condition of 25 MPa, the conductivity T of a pole piece of the positive electrode material is greater than 0.025 S / cm. The positive electrode material disclosed by the invention has relatively high pole piece conductivity, the resistance and power consumption of the prepared battery are effectively reduced, the energy transmission efficiency is improved, and in addition, the positive electrode material has the advantages of high compaction density and high material activity by limiting the quantity ratio R of the microparticles in the positive electrode material to be 8-20%; and the problems of surface side reaction increase, gas production increase and the like caused by uncontrollable number of microparticles faced by the positive electrode material are solved, and the safety and cycle performance are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery positive electrode materials, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet and a secondary battery. Background Art

[0002] With the rapid development of the global new energy materials field, the demand for lithium-ion batteries is also increasing. As a key component of battery materials, positive electrode materials are being rapidly updated. Among various positive electrode materials, ternary positive electrode materials occupy a certain market share due to their relatively high energy density. Currently, commercial ternary positive electrode materials are prone to structural collapse and intergranular cracks during the charging and discharging process, which affects the cycle life of the positive electrode materials and urgently needs to be improved. Summary of the invention

[0003] In view of this, in order to solve at least one of the above defects, it is necessary to provide a positive electrode material.

[0004] In addition, it is also necessary to provide a method for preparing the aforementioned positive electrode material, and a positive electrode sheet and a secondary battery using the aforementioned positive electrode material.

[0005] In the first aspect, an embodiment of the present application provides a positive electrode material. In an image under a scanning electron microscope at a magnification of 3k, the number of particles less than 1 μm in the positive electrode material satisfies the following ratio R: 8%≤R≤20%; and under the condition of 25 MPa, the electrode sheet conductivity T of the positive electrode material satisfies the following ratio T>0.025S / cm.

[0006] In some possible embodiments, under a scanning electron microscope at a magnification of 3k, the positive electrode material has a first region and a second region, the first region has particles with a size of less than 1 μm accounting for R1, and the second region has particles with a size of less than 1 μm accounting for R2, wherein |R1-R2|≤9% and / or 0.5≤R1 / R2≤2.

[0007] In some possible embodiments, the two sides of the peak of the particle size distribution curve of the positive electrode material are asymmetric, and the area on the left side of the peak is larger than the area on the right side of the peak.

[0008] In some possible embodiments, the positive electrode material is a single crystal positive electrode material, and an average particle size of a single particle in the positive electrode material is 1 μm to 4 μm.

[0009] In some possible embodiments, the general formula of the positive electrode material is as follows: Li a Ni b Co c Q d M (1-a-b-c-d )N eO2, wherein the Q element is selected from at least one of Mn and Al, the M element is selected from at least one of Zr, Ti, Al, Mg and Y, the N element is selected from at least one of Zr, Ti, Al, Co, Mg, W, Ce, Y, K and Na, 0.95≤a≤1.2, 0<b≤1, 0≤c≤1, 0<d≤1, b+c+d+e≤1, 0≤e<1.

[0010] In some possible embodiments, the median particle size D50 of the positive electrode material is 2.5 μm to 5 μm, D10 is 1 μm to 2.5 μm, D90 is 6 μm to 10 μm, and 1.0≤(D90-D10) / D50≤1.5.

[0011] In some possible embodiments, the specific surface area of ​​the positive electrode material is 0.5 m 2 / g~1.4 m 2 / g.

[0012] In some possible embodiments, the compaction density of the positive electrode material is greater than 3.0 g / cm 3 .

[0013] In some possible embodiments, the tap density of the positive electrode material is greater than 1.5 g / cc.

[0014] In some possible embodiments, the bulk density of the positive electrode material is greater than 0.5 g / cm 3 .

[0015] In some possible embodiments, the discharge specific capacity of the positive electrode material at 0.1C and 2.8V-4.35V is greater than 175 mAh / g.

[0016] In the second aspect, an embodiment of the present application also provides a method for preparing a positive electrode material, comprising the following steps: mixing an oxide precursor with a lithium source and a dopant and sintering the mixture to obtain a positive electrode material matrix; and crushing the positive electrode material matrix and coating the matrix with a coating agent to obtain the positive electrode material, wherein in an image under a scanning electron microscope at a magnification of 3k, the number of particles less than 1 μm in the positive electrode material satisfies R: 8%≤R≤20%; and under 25 MPa conditions, the electrode sheet conductivity T of the positive electrode material satisfies: T>0.025S / cm.

[0017] In some possible embodiments, in the step of atomizing and pyrolyzing the metal mixed solution to obtain the oxide precursor, the total metal concentration in the solution is controlled to be in the range of 2 mol / L to 8 mol / L.

[0018] In some possible embodiments, in the step of atomizing and pyrolyzing the metal mixed solution to obtain the oxide precursor, the feed flow rate is controlled to be 0.5 m³ / h~5 m³ / h.

[0019] In some possible embodiments, in the step of atomizing and pyrolyzing the metal mixed solution to obtain the oxide precursor, the atomizing air flow rate is controlled to be 50m³ / h~300m³ / h, and the atomizing pressure is controlled to be 100kPa~700kPa.

[0020] In some possible embodiments, in the step of atomizing and pyrolyzing the metal mixed solution to obtain the oxide precursor, the pyrolysis temperature is controlled to be 400° C. to 1200° C.

[0021] In some possible embodiments, the sintering includes a first sintering stage, a second sintering stage, a third sintering stage and a fourth sintering stage which are performed in sequence, the sintering temperature of the first sintering stage is 300℃~600℃, and the time is 3h~5h; the sintering temperature of the second sintering stage is 700℃~1000℃, and the time is 4h~12h; the sintering temperature of the third sintering stage is 500℃~700℃, and the time is 2h~6h; the sintering temperature of the fourth sintering stage is 700℃~1000℃, and the time is 1h~3h.

[0022] In some possible embodiments, the doping element M in the dopant is selected from at least one of Zr, Ti, Al, Mg and Y.

[0023] In some possible embodiments, the coating element N in the coating agent is selected from at least one of Zr, Ti, Al, Co, Mg, W, Ce, Y, K and Na.

[0024] In a third aspect, an embodiment of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode material as described above or a positive electrode material prepared by the positive electrode material preparation method as described above.

[0025] In a fourth aspect, an embodiment of the present application provides a secondary battery, comprising the positive electrode material as described above or a positive electrode material prepared by the method for preparing the positive electrode material as described above.

[0026] The positive electrode material provided in the embodiment of the present application has a pole sheet conductivity T under 25MPa that satisfies T>0.025S / cm. The higher pole sheet conductivity makes the positive electrode material have good electrical conductivity, which can effectively reduce the resistance and power consumption of the battery and improve the efficiency of energy transmission. Moreover, by controlling the number of microparticles in the positive electrode material to account for 8%~20%, the presence of an appropriate amount of microparticles can, on the one hand, enable the positive electrode material to have the advantages of high compaction density and high material activity at the same time, and on the other hand, it can also solve the problem of a large number of active sites of the material caused by the uncontrollable number of microparticles in the positive electrode material, reduce side reactions on the surface of the material, reduce gas production, and improve the safety and cycle performance of the battery. In addition, by controlling the number of microparticles below 1μm in the positive electrode material to account for the above range, the microparticles can also act as a buffer in the positive electrode material to disperse stress and suppress the volume change of the material caused by high conductivity during the charge and discharge process, thereby increasing the structural stability and cycle performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during charging.

[0028] Figure 2 It is a schematic cross-sectional view of a lithium-ion battery using the positive electrode material of an embodiment of the present application during discharge.

[0029] Figure 3 This is a scanning electron microscope (SEM) photograph of the oxide precursor of Example 1 of the present application.

[0030] Figure 4 This is a scanning electron microscope (SEM) photograph of the positive electrode material of Example 1 of the present application.

[0031] Figure 5 This is a particle size distribution curve of Example 1 of the present application. DETAILED DESCRIPTION

[0032] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0033] An embodiment of the present application provides a positive electrode material. In an image under a scanning electron microscope at a magnification of 3k, the number of particles less than 1 μm in the positive electrode material accounts for R: 8%≤R≤20%; and under 25 MPa conditions, the electrode sheet conductivity T of the positive electrode material satisfies: T>0.025S / cm.

[0034] By controlling the electrode conductivity T of the positive electrode material at 25MPa to satisfy T>0.025S / cm, the positive electrode material has good electrical conductivity, effectively reducing the resistance and power consumption of the prepared battery, and improving the efficiency of energy transmission. However, the higher the conductivity of the electrode sheet of the positive electrode material, the more active sites there are inside the material, and too many active sites will lead to a large number of side reactions. To this end, the embodiment of the present application limits the proportion of the number of microparticles in the positive electrode material to R of 8%-20%, so that the positive electrode material has the advantages of high compaction density and high material activity at the same time, and solves the problems of increased surface side reactions and increased gas production caused by the uncontrollable number of microparticles faced by the existing positive electrode materials, thereby improving safety and cycle performance. In addition, the inventors have found through a large number of experimental studies that by controlling the proportion of the number of microparticles below 1μm of the positive electrode material within the above range, the microparticles can also be used as buffers in the positive electrode material to disperse stress and suppress the volume change of the material caused by high conductivity during the charge and discharge process, thereby increasing the structural stability and cycle performance of the positive electrode material.

[0035] For example, the proportion of particles smaller than 1 μm in the positive electrode material may be 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, or any value within the range formed by any two of the above values. Furthermore, the proportion of particles smaller than 1 μm in the positive electrode material is 12% to 20%. Properly increasing the content of particles in the positive electrode material can promote the dispersion of stress by the particles and reduce the local stress concentration on large particles during volume change.

[0036] In some embodiments, under a scanning electron microscope (SEM) at a magnification of 3k, the positive electrode material has a first region and a second region, the first region has a number of microparticles accounting for R1, and the second region has a number of microparticles accounting for R2, wherein |R1-R2|≤9% and / or 0.5≤R1 / R2≤2. The number of microparticles in the first region and the second region is close, indicating that the microparticles are dispersed more evenly in the positive electrode material, which is beneficial to further promote the dispersion of microparticle stress and reduce the local stress concentration of large particles during volume change, thereby increasing the structural stability of the positive electrode material and improving the cycle performance of the positive electrode material.

[0037] In some embodiments, the peak of the particle size distribution curve of the positive electrode material is asymmetric, and the area on the left side of the peak is larger than the area on the right side of the peak. This indicates that the number of particles on the left side of the peak is greater than the number of particles on the right side. Specifically, particles with a particle size of less than 2 μm are defined as small particles, wherein small particles include the aforementioned microparticles, and particles with a particle size of greater than 2 μm are defined as large particles, that is, the number of small particles accounts for a greater proportion than the number of large particles, and the distribution of large and small particles is wider, which is conducive to further promoting the dispersion of stress of microparticles and reducing the local stress concentration of large particles during volume change, thereby increasing the structural stability of the positive electrode material and improving the cycle performance of the positive electrode material.

[0038] In some embodiments, the average particle size of a single particle in the positive electrode material is 1µm~4µm, and the particle is a primary particle. The presence of a certain proportion of microparticles in the positive electrode material can reduce the average particle size of the particles so that the average particle size of a single particle is within the above range, which is beneficial to the transmission of lithium ions during charging and discharging, improves ionic conductivity and thus reduces impedance; at the same time, particles in the above particle size range can control the specific surface area within an appropriate range, thereby improving the activity of the material and reducing side reactions between the material and the electrolyte.

[0039] In some embodiments, the median particle size D50 of the positive electrode material is 2.5μm~5μm, and the median particle size D50 represents the particle size of the material particles corresponding to the cumulative particle size distribution percentage reaching 50% volume ratio. The present application controls the median particle size of the positive electrode material within the above appropriate range, and the particle size is moderate, which is conducive to controlling the specific surface area of ​​the particles within a suitable range, improving the activity of the material while reducing the side reactions between the particles and the electrolyte, thereby improving the cycle life of the battery. In addition, particles of the above range size are also conducive to reducing the internal stress of the particles and reducing the risk of electrochemical polarization of lithium ions inside and outside the particles, thereby increasing the capacity of the positive electrode material. Exemplarily, the median particle size D50 of the positive electrode material can be 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm or any value within the range composed of any two of the above values.

[0040] In some embodiments, the particle size D10 of the positive electrode material is 1 μm to 2.5 μm, the particle size D90 is 6 μm to 10 μm, and 1.0≤(D90-D10) / D50≤1.5; D10 in the particle size distribution represents the particle size corresponding to the cumulative particle size distribution reaching 10%, that is, in the particle population, 10% of the particles are smaller than this particle size, and usually, D10 is used to describe the particles with finer particle size in the particle population. D90 represents the particle size corresponding to the cumulative particle size distribution reaching 90%, that is, in the particle population, 90% of the particles are smaller than this particle size, and D90 is usually used to describe the particles with coarser particle size in the particle population. (D90-D10) / D50 represents the width of the particle size distribution in the positive electrode material. In this application, by controlling 1.0≤(D90-D10) / D50≤1.5, the particle size distribution of the positive electrode material is relatively wide, which can improve the compaction density and material activity of the material while reducing the side reaction between the material and the electrolyte, thereby ensuring that the positive electrode material has high compaction density, high material activity, low impedance and excellent cycle performance. Exemplarily, (D90-D10) / D50 can be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5 or any value within the range composed of any two of the above values. D10 can be 1.0, 1.3, 1.5, 1.6, 1.8, 1.9, 2.0, 2.2, 2.3, 2.5 or any value within the range composed of any two of the above values. D90 can be 6.0, 6.3, 6.5, 6.8, 6.9, 7.0, 7.2, 7.5, 8.1, 8.5, 9.2, 10 um or any value within the range formed by any two of the above values.

[0041] In some embodiments, the positive electrode material is a single crystal positive electrode material, and the average particle size of a single particle in the positive electrode material is 1 μm to 4 μm. For example, the average particle size of a single particle can be 1 μm, 2 μm, 3 μm, 4 μm, or any value within the range formed by any two of the above values.

[0042] In some embodiments, the specific surface area of ​​the positive electrode material is 0.5 m 2 / g~1.4m 2 / g, the gaps between the large particles in the positive electrode material contain a certain number of microparticles, which can control the specific surface area within the aforementioned suitable range, which is beneficial to improving the activity of the positive electrode material and reducing the side reactions between the positive electrode material and the electrolyte, which is beneficial to improving the long-term cycle performance of the positive electrode material. For example, the specific surface area of ​​the positive electrode material can be 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9 m 2 / g, 1.0m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3 m 2 / g, 1.4m 2 / g or any value within the range formed by any two of the above values.

[0043] In some embodiments, the compaction density of the positive electrode material is greater than 3.0 g / cm 3 By controlling the number of microparticles in the positive electrode material to 8%~20%, it can be ensured that during the rolling process of the positive electrode material, when the positive electrode material is subjected to external force, the microparticles fill the gaps between the large particles, thereby improving the uniform distribution of the microparticles in the positive electrode material, promoting the microparticles to disperse stress, and reducing the local stress concentration on the large particles during the volume change process, thereby increasing the structural stability of the positive electrode material and improving the cycle performance of the positive electrode material.

[0044] In some embodiments, the tap density of the positive electrode material is > 1.5 g / cm 3 By controlling the number of microparticles in the positive electrode material to 8%~20%, the tap density of the positive electrode material can be effectively improved, which is beneficial to improving the capacity and cycle performance of the battery.

[0045] In some embodiments, the bulk density of the positive electrode material is greater than 0.5 g / cm 3 By controlling the number of microparticles in the positive electrode material to 8%~20%, the bulk density of the material can be controlled to >0.5g / cm 3 The loose density is appropriate, which can effectively improve the capacity density of the battery while reducing the possibility of peeling of the active material during charging and discharging, which is beneficial to improving the battery capacity and cycle life.

[0046] In some embodiments, the general formula of the positive electrode material is as follows: Li a Ni b Co c Q d M (1-b-c-d )N e O2, wherein the Q element is selected from at least one of Mn and Al, the M element is selected from at least one of Zr, Ti, Al, Mg and Y, the N element is selected from at least one of Zr, Ti, Al, Co, Mg, W, Ce, Y, K and Na, 0.95≤a≤1.2, 0<b≤1, 0≤c≤1, 0<d≤1, b+c+d+e≤1, 0≤e<1.

[0047] The positive electrode material provided in the embodiment of the present application satisfies T>0.025S / cm at 25MPa. The higher the pole sheet conductivity, the better the conductivity of the positive electrode material, which effectively reduces the resistance and power consumption of the prepared battery and improves the efficiency of energy transmission. However, the higher the pole sheet conductivity of the positive electrode material, the more active sites there are inside the material, and too many active sites will lead to a large number of side reactions. To this end, the embodiment of the present application limits the proportion of the number of microparticles in the positive electrode material to R of 8%-20%, so that the positive electrode material has the advantages of high compaction density and high material activity at the same time, and solves the problems of uncontrollable number of microparticles in the positive electrode material, which leads to increased surface side reactions and increased gas production, thereby improving safety and cycle performance. In addition, by controlling the proportion of the number of microparticles below 1μm in the positive electrode material within the above range, the microparticles can also act as a buffer in the positive electrode material to disperse stress and suppress the volume change of the material caused by high conductivity during the charge and discharge process, thereby increasing the structural stability and cycle performance of the positive electrode material.

[0048] It should be noted that the difference between single crystal positive electrode materials and polycrystalline positive electrode materials (i.e., polycrystalline secondary particles) is that the smallest particle of polycrystalline secondary particles is a secondary particle formed by the agglomeration of nanometer-scale primary particles. For single crystal positive electrode materials, the smallest particle is usually a single primary particle of micrometer scale. Generally speaking, in addition to the EBSD test method, it is also possible to determine whether the obtained positive electrode product is a single crystal material by characterization methods such as scanning electron microscopy (SEM). For example, for single crystal positive electrode materials, the morphology of single crystal particles can be characterized by SEM, and it can be seen that the shape of single crystal particles is generally regular or irregular spherical, and there is no significant particle agglomeration. The orientation of single crystal positive electrode materials can also be characterized by EBSD. Through EBSD, it can be observed that the color in at least one grain is the same, so as to judge that the orientation in at least one grain is the same, and the grains with the same orientation are single crystals. It should be specifically noted that the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict crystallographic sense. In crystallography, an ideal single crystal refers to a crystal with completely the same arrangement and direction. However, due to impurities, strains and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal cathode materials known in the art are actually more "single crystal morphology" cathode materials, which only show the size of large single crystal particles and are different from polycrystalline particles composed of many small primary particles.

[0049] It can be understood that a single grain in the present application can be a single particle composed of a primary particle. The above-mentioned single crystal positive electrode material may also contain a small amount of "quasi-secondary particles" formed by the adhesion of several single particles. "Primary particle" refers to the smallest particle unit identified when observing the positive electrode active material through a scanning electron microscope, and "secondary particle" refers to a secondary structure formed by the agglomeration of multiple primary particles, showing a relatively rounded spherical morphology. "Quasi-secondary particles" refer to those formed by the adhesion of several single particles. Usually, the particle size of a single particle in the above-mentioned quasi-secondary particles is usually between 1μm and 5μm. In general, the roundness of the particles of "quasi-secondary particles" is lower than that of the above-mentioned conventional "secondary particles".

[0050] It should be further explained that the "single crystal" in the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict sense. In crystallography, an ideal single crystal refers to a crystal with exactly the same arrangement and orientation. However, due to impurities, strain and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal positive electrode materials known in the art are actually more of "single crystal-like morphology" positive electrode materials, which only show a large particle size similar to a single crystal in size, which is different from a polycrystal composed of many small primary particles.

[0051] The present application also provides a method for preparing the aforementioned positive electrode material, which specifically comprises the following steps: Step S1, atomizing and pyrolyzing the metal mixed solution to obtain an oxide precursor.

[0052] Specifically, solutions of a nickel source, a cobalt source and a manganese source or an aluminum source are mixed, and the mixture is atomized and then thermally decomposed to obtain an oxide precursor.

[0053] In some embodiments, the nickel source, cobalt source, manganese source or aluminum source can be sulfate, hydrochloride, nitrate, acetate solution, etc. of the corresponding metal elements.

[0054] In some embodiments, the total metal concentration in the aforementioned mixed solution is controlled to be 2mol / L~8mol / L. By controlling the total metal concentration within the above range, the particle size of the primary particles of the oxide precursor can be controlled, so that the particle size distribution of the primary particles of the precursor is wider, which is conducive to the formation of microparticles in the positive electrode material. Exemplarily, the total metal concentration in the solution can be 2mol / L, 3mol / L, 4mol / L, 5mol / L, 6mol / L, 7mol / L, 8mol / L or any value within the range composed of any two of the above values.

[0055] In some embodiments, the feed flow rate is 0.5m³ / h~5m³ / h. By controlling the feed flow rate within the above range, the growth rate of the precursor particles can be effectively controlled to form primary particles of suitable particle size, so as to reduce the activity of the precursor particles and facilitate the formation of microparticles in the positive electrode material. Exemplarily, the feed flow rate can be 0.5m³ / h, 1m³ / h, 15m³ / h, 2m³ / h, 2.5m³ / h, 3m³ / h, 35m³ / h, 4m³ / h, 4.5m³ / h, 5m³ / h or any value within the range formed by any two of the above values.

[0056] In some embodiments, during the spray pyrolysis process, the atomizing air flow rate is controlled to be 50m³ / h~300m³ / h, and the atomizing pressure can be 100kPa~700kPa. Since the size of the precursor particles is directly related to the subsequent reaction activity with the lithium source, the larger the particles, the weaker the activity. Therefore, by controlling the atomizing air flow rate and the atomizing pressure, the atomizing intensity can be controlled, and then the various components in the mixture can be fully decomposed and reacted to control the primary particle formation rate of the precursor, and control the primary particle size of the precursor within an appropriate range, thereby reducing the subsequent reaction activity of the particles with the lithium source, which is beneficial to the formation of microparticles in the positive electrode material. Further, the atomizing air flow rate may be 100m³ / h~200m³ / h, and illustratively, the atomizing air flow rate may be 50m³ / h, 80m³ / h, 100m³ / h, 120m³ / h, 150m³ / h, 180m³ / h, 200m³ / h, 230m³ / h, 270m³ / h, 300m³ / h, or any value within the range formed by any two of the above values. Further, the atomizing pressure may be 100kPa~400kPa, and illustratively, the atomizing pressure may be 100kPa, 200kPa, 300kPa, 400kPa, 500kPa, 600kPa, 700kPa, or any value within the range formed by any two of the above values.

[0057] In some embodiments, the nozzle diameter may be 0.1 mm to 20 mm. By controlling the nozzle diameter, the formation rate of the precursor and the size of the primary particles may also be regulated. For example, the nozzle diameter may be 0.1 mm, 1 mm, 3 mm, 5 mm, 8 mm, 10 mm, 12 mm, 14 mm, 16 mm, 18 mm, 20 mm, or any value within the range of any two of the above values.

[0058] In some embodiments, the pyrolysis temperature is controlled to be 400°C to 1200°C. Since the uncontrollable microparticles in the positive electrode material will lead to an increase in side reactions on the surface of the material, the present application can appropriately suppress the increase in the particle size of the precursor primary particles by regulating the pyrolysis temperature within the above range, so that the activity of the primary particles is enhanced, and particles with larger particle sizes are formed when reacting with lithium salts, thereby suppressing the formation of microparticles to a certain extent, so as to achieve the purpose of regulating the proportion of the number of microparticles in the positive electrode material, realize the controllable number of microparticles, and improve the activity of the positive electrode material while reducing the occurrence of side reactions.

[0059] In some embodiments, during the pulverization process of the oxide precursor, by controlling the frequency of the classifier during the air flow pulverization process at 30HZ~50HZ and the air pressure at 300kPa~500kPa, the size of the primary particles of the precursor can be further appropriately reduced to increase the activity of the primary particles, and the formation of microparticles can be further inhibited when reacting with lithium salts, thereby controlling the proportion of the number of microparticles to be within an appropriate range.

[0060] Step S2, mixing the oxide precursor with the lithium source and the dopant and sintering (defined as primary sintering here) to obtain a positive electrode material matrix.

[0061] The primary sintering includes a first sintering stage, a second sintering stage, a third sintering stage and a fourth sintering stage which are performed in sequence.

[0062] In some embodiments, the temperature T1 of the first sintering stage is 300°C to 600°C, and the time is 3h to 5h. The material is first heated to a lower temperature stage, so that the lithium salt can be fully melted and the dopant can be evenly diffused in the mixture. Exemplarily, the temperature of the first sintering stage can be 300°C, 400°C, 500°C, 600°C or any value in the range of any two of the above values; the sintering time can be 3h, 4h, 5h or any value in the range of any two of the above values.

[0063] In some embodiments, the temperature T2 of the second sintering stage is 700°C to 1000°C, and the time is 4h to 12h. This stage is the main stage of crystal formation and crystal growth. By controlling the sintering temperature and sintering time within the above range, the embedding of lithium ions can be achieved, the growth of crystals can be promoted, and the rate and size of particle size growth can be controlled. Exemplarily, the temperature of the second sintering stage can be 700°C, 800°C, 900°C, 1000°C or any value in the range composed of any two of the above values; the sintering time can be 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h or any value in the range composed of any two of the above values.

[0064] In some embodiments, the sintering temperature T3 of the third sintering stage is 500°C~700°C, and the time is 2h~6h. After high-temperature sintering, by controlling the temperature and time of low-temperature sintering within the above range, lithium ions can be further embedded, while suppressing the growth of particle size and controlling the particle size to form microparticles with the required number proportion. In addition, low-temperature sintering also has the effect of annealing, effectively eliminating lattice internal stress, repairing micrograin boundaries, and reducing particle defects. Exemplarily, the temperature of the third sintering stage can be 500°C, 600°C, 700°C or any value in the range composed of any two of the above values; the sintering time can be 2h, 3h, 4h, 5h, 6h or any value in the range composed of any two of the above values.

[0065] In some embodiments, the sintering temperature T4 of the fourth sintering stage is 700°C~1000°C, and the time is 1h~3h. If the low-temperature sintering is too thick, a short-time high-temperature re-firing can further increase the embedding of lithium ions and further improve the crystal structure. Exemplarily, the temperature of the fourth sintering stage can be 700°C, 800°C, 900°C, 1000°C or any value in the range of any two of the above values; the sintering time can be 1h, 2h, 3h or any value in the range of any two of the above values.

[0066] In some embodiments, the total sintering time can be 12 to 26 hours. By controlling the total sintering time, the particle size can be controlled, and the number of microparticles formed can be controlled to account for 8% to 20%. Exemplarily, the total sintering time can be 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 21 hours, 22 hours, 23 hours, 24 hours, 25 hours, 26 hours, or any value within the range consisting of any two of the above values.

[0067] In some embodiments, the temperature is increased from room temperature to the first sintering stage at a heating rate of 20°C / min, and increased from the first sintering stage to the second sintering stage at a heating rate of 0.5~3°C / min, and then decreased to the third sintering stage at a cooling rate of 0.5~3°C / min, and then increased to the fourth sintering stage at a heating rate of 0.5~3°C / min, and finally decreased from the fourth sintering stage to room temperature at a cooling rate of 0.5~3°C / min to obtain a positive electrode material matrix.

[0068] In some embodiments, the sintering atmosphere may be an oxygen atmosphere or an air atmosphere.

[0069] In some embodiments, the doping element M in the dopant is selected from at least one of Zr, Ti, Al, Mg and Y. The dopant may be an oxide of the aforementioned doping element or a lithium ion conductor.

[0070] In some embodiments, the content of the dopant is 200 ppm to 10000 ppm. For example, the content of the dopant is 200 ppm, 300 ppm, 400 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, 1000 ppm or any value in the range consisting of any two of the above values.

[0071] In some embodiments, the lithium source may be LiOH.H2O, Li2CO3, or a mixture of LiOH.H2O and Li2CO3.

[0072] In some embodiments, the molar ratio of the lithium content in the lithium salt to the nickel, cobalt and manganese content in the precursor is 0.98 to 1.10.

[0073] In some embodiments, the particle size D50 of the lithium salt may be 5 μm to 30 μm.

[0074] In this step, low-temperature sintering is first performed to achieve full melting of the lithium salt and uniform diffusion of the dopant; the subsequent high-temperature sintering achieves the embedding of lithium ions and the initial growth of particles; the subsequent low-temperature sintering can further embed lithium ions, control the particle size of the particles, and is conducive to the formation of microparticles, while also playing a role in annealing and repairing microcrystalline boundaries; finally, short-term high-temperature sintering can further promote the embedding of lithium ions and further regulate the proportion of microparticles.

[0075] Step S3, crushing the positive electrode material matrix and coating it with a coating agent to obtain the positive electrode material, wherein in the image under a scanning electron microscope at a magnification of 3k, the number of microparticles below 1 μm in the positive electrode material accounts for R: 8≤%R≤20%; and under 25MPa conditions, the conductivity T of the electrode sheet prepared from the positive electrode material satisfies: T>0.025S / cm.

[0076] Specifically, the positive electrode material matrix obtained by the previous sintering is crushed, and the particle size distribution of the matrix is ​​adjusted by controlling the frequency of the classifier in the air flow crushing equipment to 40HZ~60HZ and the air pressure to 400kPa~600kPa. The crushed positive electrode material matrix is ​​subjected to a primary coating and a secondary sintering to obtain a primary coating material. The primary coating material is subjected to a secondary coating and a tertiary sintering, and then sieved and ground to finally obtain the positive electrode material. After two coating and sintering, the coating agent can be evenly coated on the surface of the positive electrode material matrix for surface modification, so as to further improve the structural stability and electrochemical performance of the positive electrode material.

[0077] The coating element N in each coating agent can be selected from at least one of Zr, Ti, Al, Co, Mg, W, Ce, Y, K, Na, etc., wherein the coating agent can be an oxide of the coating element N or a lithium ion conductor.

[0078] In some embodiments, the temperature of the secondary sintering can be 400-600°C, and the sintering time can be 6-12h. The temperature of the tertiary sintering can be 400-600°C, and the sintering time can be 6h-10h. By controlling the temperature and time of the secondary sintering and the tertiary sintering, the coating agent can be evenly coated on the surface of the substrate in batches, further optimizing the surface structure of the positive electrode material, so as to further improve the structural stability and conductivity of the positive electrode material. Exemplarily, the temperature of the secondary sintering can be 400°C, 500°C, 600°C or any value in the range of any two values ​​above, and the sintering time can be 6h, 7h, 8h, 9h, 10h, 11h, 12h or any value in the range of any two values ​​above; the temperature of the tertiary sintering can be 400°C, 500°C, 600°C or any value in the range of any two values ​​above, and the sintering time can be 6h, 7h, 8h, 9h, 10h or any value in the range of any two values ​​above.

[0079] In some embodiments, the content of the coating element may be 200ppm to 5000ppm. For example, the content of the coating element may be 200ppm, 500ppm, 800ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm or any value within the range consisting of any two of the above values.

[0080] The hydroxide precursor prepared by the traditional coprecipitation method has low crystallinity and poor tolerance to doping with large-radius elements. High-valent elements easily adhere to the surface of the material, thereby inhibiting the crystal from growing into single crystal particles with good dispersion. For this reason, the preparation method of the positive electrode material provided in the embodiment of the present application adopts spray pyrolysis technology to prepare the oxide precursor, while appropriately reducing the reactivity of the oxide precursor, and then reacting the oxide precursor with the lithium salt through multi-temperature stage sintering to prepare the positive electrode material containing an appropriate amount of microparticles.

[0081] First, unlike hydroxide precursors, oxide precursors have a certain crystal structure and are a two-phase mixture of spinel and rock salt phases. Oxide precursors have a larger diffusion width when sintering with lithium salts, and a relatively wider particle size distribution is conducive to the formation of an appropriate number of microparticles. In other words, the particle size distribution of the prepared oxide precursor is wider, and the reaction activity with lithium salts is lower, so that the crystal particles are not fully diffused when growing into single crystals. Some particles are not sufficiently single-crystallized and will form microparticles with smaller particle sizes. By controlling the width of the particle size distribution of the aforementioned oxide precursor, the number of microparticles formed during the sintering process can be controlled within a suitable range of 8% to 20%, thereby improving the compaction density and energy density of the material. Moreover, the particle size distribution of the positive electrode material has good inheritance. The positive electrode material can well inherit the particle size distribution of the matrix, and the matrix can also inherit the particle size distribution of the oxide precursor to a certain extent.

[0082] Secondly, the appropriate proportion of microparticles is conducive to a more complete combination of the material and the conductive agent, reducing the proportion of micropores in the material. At the same time, coating the matrix material with N elements can also effectively improve the conductivity of the active material, thereby making the positive electrode material have a higher electrode conductivity.

[0083] In addition, the preparation method of the embodiment of the present application has a short reaction time, has the advantages of short-range high efficiency, low processing cost, low raw material cost, less pollution, no wastewater generation, and high recycling rate, etc., and is suitable for industrial large-scale production.

[0084] An embodiment of the present application also provides a positive electrode sheet using the aforementioned positive electrode material, comprising a positive electrode collector and a positive electrode active material layer disposed on at least one surface of the positive electrode collector, wherein the positive electrode active material layer comprises the aforementioned positive electrode material.

[0085] The positive electrode current collector may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.

[0086] The present application also provides a secondary battery (such as a lithium-ion battery, a sodium-ion battery, etc.), including a housing, an electrode assembly and an electrolyte / electrolyte. The electrode assembly and the electrolyte / electrolyte are both located in the housing. The electrode assembly includes a separator, a negative electrode sheet and the positive electrode sheet, and the separator is disposed between the positive electrode sheet and the negative electrode sheet.

[0087] In some embodiments, the outer shell may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), such as a soft-pack battery. In other embodiments, the secondary battery may also be a steel-shell battery, an aluminum-shell battery, or the like.

[0088] In some embodiments, the electrode assembly may be a laminated structure, which is formed by alternately stacking a positive electrode sheet, a separator, and a negative electrode sheet. In other embodiments, the electrode assembly may also be a wound structure, which is formed by stacking a positive electrode sheet, a separator, and a negative electrode sheet in sequence and then winding them.

[0089] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode current collector may use at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, etc., or may be a composite current collector disclosed in any prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more. The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium-ion battery, a sodium-ion battery, a solid electrolyte battery, etc., without limitation herein.

[0090] like Figure 1 and Figure 2 As shown in the figure, they are schematic diagrams of lithium removal and lithium insertion during the charging and discharging process of a lithium-ion battery prepared by using the positive electrode material provided in the embodiment of the present application. Figure 1 As shown in , when a lithium-ion battery is charged, lithium ions are released from the positive electrode and embedded in the negative electrode; Figure 2 As shown, when a lithium-ion battery is discharged, lithium ions are released from the negative electrode and embedded back into the positive electrode.

[0091] The embodiment of the present application prepares a secondary battery by using the aforementioned positive electrode material, and controls the number of microparticles in the positive electrode material to account for 8% to 20%, and the conductivity of the positive electrode sheet at 25MPa is T>0.025S / cm. The positive electrode material has both high compaction density and high material activity, which improves the capacity and activity of the secondary battery; and by limiting the number of microparticles in the positive electrode material to account for 8%-20%, the positive electrode material has the advantages of high compaction density and high material activity, and solves the problems of the uncontrollable number of microparticles in the existing positive electrode material, which leads to increased surface side reactions and increased gas production, thereby improving safety and cycle performance. In addition, by controlling the number of microparticles below 1μm in the positive electrode material to account for the above range, the microparticles can also act as a buffer in the positive electrode material, play a role in dispersing stress, and inhibit the volume change of the material caused by high conductivity during the charge and discharge process, thereby increasing the structural stability and cycle performance of the positive electrode material. The secondary battery using the above-mentioned positive electrode material has a discharge specific capacity of 2.8V~4.35V at 0.1C>175mAh / g, and a cycle retention rate of 0.5C charging and 1C discharging for 50 weeks>95%.

[0092] The scheme of the present application will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present application and cannot be construed as limiting the present application. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.

[0093] Embodiment 1: Step 1, prepare a metal salt mixed solution according to the molar ratio of Ni:Co:Mn:50:20:30, control the total metal concentration in the solution to 2mol / L, control the feed flow rate to 1.2m³ / h, control the atomizing air flow rate to 150m³ / h, control the atomizing air pressure to 300kPa, select a nozzle with a diameter of 10mm, control the pyrolysis temperature to 550℃, and calcine in an air atmosphere to obtain a precursor. The precursor is air flow crushed, and the classifier frequency is controlled to 40HZ and the air pressure is controlled to 400KPa during the crushing process to obtain an oxide precursor with a particle size of D50=4.1μm, and its main element chemical composition can be expressed as Ni 0.50 Co 0.20 Mn 0.30 O 1.2 (The content deviation of each element is within ±1%).

[0094] Step 2: Evenly mix the oxide precursor prepared in step 1 with LiOH·H2O at a molar ratio of 1:1.03, wherein the average particle size of LiOH·H2O is 13 μm. Based on the mass of the oxide precursor, 1200 ppm of nano-ZrO2 is added.

[0095] Step 3, placing the mixture of step 2 in an atmosphere furnace, under an oxygen atmosphere, ① at a heating rate of 20℃ / min, from room temperature to the first sintering stage temperature: 300℃, keep warm for 3h; ② at a heating rate of 3℃ / min, from the first sintering stage to the second sintering stage temperature: 800℃, keep warm for 5h; ③ at a cooling rate of 2℃ / min, from the second sintering stage to the third sintering stage temperature: 600℃, keep warm for 4h; ④ at a heating rate of 3℃ / min, the third sintering stage is heated again to the fourth sintering stage temperature: 960℃, keep warm for 3h; ⑤ at a cooling rate of 3℃ / min, from the fourth sintering stage to room temperature. During the sintering process, the oxygen flow rate is controlled to be 0.14m³ / min, and the furnace pressure is 7Pa to obtain the positive electrode material matrix (LiNi 0.50 Co 0.20 Mn 0.30 O2).

[0096] Step 4, the positive electrode material matrix of step 3 is coarsely crushed by a roller mill to obtain a coarse particle sample with an average particle size of 10μm~20μm, and the coarse particle sample is crushed by a jet mill to obtain a sample with a D50 of 4.3μm, wherein the grinding air pressure during the jet milling process is 600kPa and the classifier frequency is 52HZ.

[0097] Step 5, mixing the sample in step 4 with 1000 ppm of nano-sized Al2O3, heating to 450°C at a rate of 4°C / min in an oxygen atmosphere and keeping the temperature for 6 hours to obtain a primary coated material.

[0098] Step 6, after uniformly mixing the primary coating material in step 5 with 800 ppm of NaOH and KOH, heating to 400° C. at a rate of 4° C. / min in an oxygen atmosphere and keeping the temperature for 6 hours to obtain a secondary coating material.

[0099] Step 7, screening and grinding the secondary coating material in step 6 for 30 minutes to obtain a positive electrode material.

[0100] Example 2 The difference from Example 1 is that in step 1, the atomizing air flow rate is adjusted to 120 m³ / h, and the atomizing air pressure is adjusted to 250 kPa. The other steps are basically the same as those in Example 1, please refer to Example 1.

[0101] Example 3 The difference from Example 1 is that in step 1, the pyrolysis temperature is 500° C. The other steps are basically the same as those in Example 1, please refer to Example 1.

[0102] Example 4 The difference from Example 1 is that in step 1, the frequency of the classifier in the process of crushing the large-particle oxide precursor is adjusted to 45HZ to obtain a precursor with a particle size D50=3.5μm. The other steps are basically the same as Example 1, please refer to Example 1.

[0103] Example 5 The difference from Example 1 is that in step 3, ① the temperature is increased from room temperature to the temperature of the first sintering stage: 300°C at a heating rate of 20°C / min, and kept warm for 3 hours; ② the temperature is increased from the first sintering stage to the temperature of the second sintering stage: 800°C at a heating rate of 3°C / min, and kept warm for 5 hours; ③ the temperature is decreased from the second sintering stage to the temperature of the third sintering stage: 600°C at a cooling rate of 2°C / min, and kept warm for 4 hours; ④ the temperature is increased again from the third sintering stage to the temperature of the fourth sintering stage: 990°C at a heating rate of 3°C / min, and kept warm for 3 hours; ⑤ the temperature is decreased from the fourth sintering stage to room temperature at a cooling rate of 3°C / min.

[0104] The other steps are basically the same as those in Example 1, please refer to Example 1.

[0105] Example 6 The difference from Example 1 is that in step 3, ① the temperature is increased from room temperature to the temperature of the first sintering stage: 300°C at a heating rate of 20°C / min, and kept warm for 3 hours; ② the temperature is increased from the first sintering stage to the temperature of the second sintering stage: 800°C at a heating rate of 3°C / min, and kept warm for 5 hours; ③ the temperature is decreased from the second sintering stage to the temperature of the third sintering stage: 600°C at a cooling rate of 2°C / min, and kept warm for 4 hours; ④ the temperature is increased again from the third sintering stage to the temperature of the fourth sintering stage: 930°C at a heating rate of 3°C / min, and kept warm for 3 hours; ⑤ the temperature is decreased from the fourth sintering stage to room temperature at a cooling rate of 3°C / min.

[0106] In step 7, the grinding time is 10 min.

[0107] The other steps are basically the same as those in Example 1, please refer to Example 1.

[0108] Example 7 The difference from Example 1 is that in step 5, the coating agent is 1000 ppm of WO3.

[0109] In step 6, the total coating amount of NaOH and KOH is increased to 1000 ppm.

[0110] The other steps are basically the same as those in Example 1, please refer to Example 1.

[0111] Example 8 The difference from Example 1 is that in step 3, the lithium source is Li2CO3 and the sintering atmosphere is air atmosphere.

[0112] The other steps are basically the same as those in Example 1, please refer to Example 1.

[0113] Example 9 The difference from Example 1 is that in step S3, the lithium source is a mixture of Li2CO3:LiOH·H2O=1:1, and the sintering atmosphere is air atmosphere.

[0114] The other steps are basically the same as those in Example 1, please refer to Example 1.

[0115] Example 10 The difference from Example 1 is that in step 3, the gas flow rate is increased to 0.18 m³ / min and the furnace pressure is 10 Pa.

[0116] The other steps are basically the same as those in Example 1, please refer to Example 1.

[0117] Embodiment 11 The difference from Example 8 is that in step 1, the molar ratio of Ni:Co:Mn is controlled to be 60:10:30, and the oxide precursor Ni is obtained by pyrolysis. 0.60 Co 0.10 Mn 0.30 O 1.2 ; In step 3, ④ the temperature is raised again in the third sintering stage to the fourth sintering stage temperature: 920℃ at a heating rate of 3℃ / min, and kept warm for 3h. The element composition of the obtained positive electrode material is LiNi 0.60 Co 0.10 Mn 0.30 O2.

[0118] The other steps are basically the same as those in Example 8, please refer to Example 8.

[0119] Example 12 The difference from Example 8 is that the molar ratio of Ni:Co:Mn is controlled to be 80:10:10, and the oxide precursor Ni is obtained by pyrolysis. 0.80 Co 0.10 Mn 0.10 O 1.2 ; In step 3, ④ the temperature is raised again to the fourth sintering stage temperature of 880℃ at a heating rate of 3℃ / min, and kept warm for 3h. The element composition of the obtained positive electrode material is LiNi 0.80 Co 0.10 Mn 0.10 O2.

[0120] The other steps are basically the same as those in Example 8, please refer to Example 8.

[0121] Example 13 The difference from Example 8 is that the molar ratio of Ni:Co:Mn is controlled to be 82.5:6.5:11, and the oxide precursor Ni is obtained by pyrolysis. 0.825 Co 0.065 Mn 0.11 O 1.2 ; In step 3, ④ the temperature is raised again to the fourth sintering stage temperature of 870℃ at a heating rate of 3℃ / min, and kept at this temperature for 3h. The chemical formula of the positive electrode material obtained is LiNi 0.825 Co 0.065 Mn 0.11 O2.

[0122] The other steps are basically the same as those in Example 8, please refer to Example 8.

[0123] Embodiment 14 The difference from Example 1 is that in step 2, the precursor used is the oxide precursor Ni prepared in step 1 of Example 1. 0.50 Co 0.20 Mn 0.30 O 1.2 With the hydroxide precursor Ni 0.50 Co 0.20 Mn 0.30 A mixture of (OH)2, the molar ratio of the oxide precursor to the hydroxide precursor is 1:1. This hydroxide precursor is prepared by the traditional co-precipitation method, and the preparation method is as follows: a certain concentration of salt solution (such as NiSO4, CoSO4, MnSO4, etc.) and an alkaline solution (such as NaOH, NH3, etc.) are continuously added to the reactor at a certain flow rate. The reaction is carried out at an appropriate reaction temperature (40~60℃), stirring rate, and pH value (10~13) to generate a hydroxide precipitate. The generated precipitate is washed, filtered, dried, and finally a hydroxide precursor material is obtained.

[0124] Step 2 also includes the following steps: the precursor mixture is uniformly mixed with LiOH·H2O at a molar ratio of 1:1.05, and 1200 ppm of ZrO2 is added relative to the mass of the precursor.

[0125] Step 3 also includes the following steps: in an oxygen atmosphere, ① at a heating rate of 20℃ / min, from room temperature to the first sintering stage temperature: 300℃, keep warm for 3h; ② at a heating rate of 3℃ / min, from the first sintering stage to the second sintering stage temperature: 800℃, keep warm for 7h; ③ at a cooling rate of 2℃ / min, from the second sintering stage to the third sintering stage temperature: 600℃, keep warm for 4h; ④ at a heating rate of 3℃ / min, the third sintering stage is heated again to the fourth sintering stage temperature: 960℃, keep warm for 3h; ⑤ at a cooling rate of 3℃ / min, from the fourth sintering stage to room temperature. During the sintering process, the oxygen flow rate is controlled to be 0.20m³ / min, and the furnace pressure is 10Pa to obtain the positive electrode material matrix (LiNi 0.50 Co 0.20 Mn 0.30 O2).

[0126] The other steps are basically the same as those in Example 1, please refer to Example 1.

[0127] Embodiment 15 The difference between this embodiment and embodiment 12 is that the metal salt mixed solution is prepared according to the molar ratio of Ni:Co:Al of 80:10:10, and the element composition of the obtained positive electrode material is LiNi 0.80 Co 0.10 Al 0.10 O2.

[0128] The other steps are basically the same as those in Example 12, please refer to Example 12.

[0129] Comparative Example 1 The difference from Example 4 is that in step 4, during the crushing of the positive electrode material matrix, the grinding gas pressure is 600 kPa and the classifying wheel frequency is 60 Hz.

[0130] The other steps are basically the same as those in Example 4, please refer to Example 4.

[0131] Comparative Example 2 The difference from Example 1 is that in step 3, ① the temperature is raised from room temperature to the first sintering stage temperature: 300℃ at a heating rate of 20℃ / min, and kept warm for 3h; ② the temperature is raised from the first sintering stage to the second sintering stage temperature: 700℃ at a heating rate of 3℃ / min, and kept warm for 5h; ③ the temperature is lowered from the second sintering stage to the third sintering stage temperature: 500℃ at a cooling rate of 2℃ / min, and kept warm for 4h; ④ the temperature is raised again from the third sintering stage to the fourth sintering stage temperature: 820℃ at a heating rate of 3℃ / min, and kept warm for 3h; ⑤ the temperature is lowered from the fourth sintering stage to room temperature at a cooling rate of 3℃ / min. The positive electrode material LiNi 0.5 Co 0.2Mn 0.3 O2 presents a polycrystalline morphology.

[0132] The other steps are basically the same as those in Example 1, please refer to Example 1.

[0133] Comparative Example 3 The difference from Example 1 is that in step 2, the coprecipitated hydroxide precursor in Example 14 is selected as the raw material, and its chemical formula is Ni 0.50 Co 0.2 Mn 0.3 (OH)2. The formed positive electrode material presents a single crystal morphology.

[0134] The other steps are basically the same as those in Example 1, please refer to Example 1.

[0135] The following method was used to test the performance of the positive electrode materials obtained in the above Examples 1-15 and Comparative Examples 1-3.

[0136] 1. Characterization of the proportion of micro powder: Sample preparation: Use tweezers or other tools to pick up the powder sample, spread it on the conductive glue and flatten it, and test it under 5kV / 10mA electron beam conditions. When testing the cross-section sample, the material is coated on aluminum foil using the conventional electrode preparation process, then cut using a focused ion beam (FIB), and then tested under the same conditions as the powder sample under SEM.

[0137] Characterization: The single crystal particle size in the scanning electron microscope (SEM) image can be identified by software. Take a photo at 3K magnification. Measure the longest diameter of all particles in the photo and count the size of each particle. The total number of single particles is recorded as N, and the number of particles with a diameter less than 1μm is recorded as n. R is the percentage of the number of microparticles, where R=n / N*100%.

[0138] 2. Specific surface area characterization: Equipment: Specific surface area and pore structure analyzer.

[0139] Method: Weigh the mass of the empty sample tube m1; take 3g of sample and add it to the sample tube through a long-necked funnel; vacuum degas at 300℃ for 1h, and weigh the mass of the sample tube m2 after cooling; the mass of the sample is m=m2-m1. The sample tube is placed in liquid nitrogen, and the nitrogen adsorption amount V of the sample is measured at a series of relative pressures P / P0 to obtain the adsorption isotherm. Among them, P / P0 is set to 0.05 / 0.1 / 0.15 / 0.20 / 0.25 / 0.30. Fit the isothermal adsorption curve, calculate the monolayer saturated adsorption amount Vm according to the slope and intercept, and then calculate the specific surface area according to Vm.

[0140] 3. Compacted density characterization: Using the American Carver 4350 tester, 1g of sample was weighed and placed in a mold, pressed with a pressure of 3T for 30s. After pressing, the height was tested and the compacted density was calculated.

[0141] 4. Characterization of bulk density: Equipment: Bulk density meter Method: Take an appropriate amount of sample and allow it to flow naturally into the distribution box, alternately pass through four glass plates with an inclined angle of 25° and a square funnel in the distribution box, and flow into a cylindrical cup of known volume (25 ml). Finally, weigh the mass of the powder in the cylindrical cup.

[0142] 5. Tap density test: The American Quantachrome tap density tester DAT-4-220 was used.

[0143] The test steps include: clean the measuring cylinder, and then weigh the mass of the measuring cylinder as m1; add the sample to the measuring cylinder, try to make the sample surface level, and wipe the surrounding area with a paper towel; weigh the total mass of the sample and the measuring cylinder as m2; place the measuring cylinder on the vibration table and fix it with three symmetrical fixed feet; turn on the instrument, turn on the vibration switch, and the instrument will automatically stop after vibrating for a specified number of times; take out the measuring cylinder and read the volume of the sample. If the sample surface is horizontal after vibration, read the volume directly; if it is in a diagonal state, take the average value V of the readings at the highest and lowest points.

[0144] Calculation formula: tap density = (m2-m1) / V.

[0145] 6. SEM and EDS characterization: Equipment: Scanning electron microscope, energy dispersive spectrometer.

[0146] SEM test method: When testing powder samples, use tweezers or other tools to pick up the powder sample, spread it on the conductive glue and flatten it to make a test sample, and test it under 5kV / 10mA electron beam conditions. In the test of the percentage of particle number, randomly select an area of ​​the test sample as the first area, and collect the image of the first area under the electron microscope at a magnification of 3K, and calculate the percentage of particles below 1μm in the SEM image of the first area as R1; then randomly select another area of ​​the test sample as the second area, and collect the image of the second area under the electron microscope at a magnification of 3K, and calculate the percentage of particles below 1μm in the SEM image of the second area as R2. It can be understood that the aforementioned first area and second area can be multiple. The percentage of particles below 1μm R is the average percentage of particles below 1μm in n areas of the randomly selected sample, n≥10.

[0147] EDS test method: Adjust the electron beam voltage of SEM to above 15kV, and then use EDS to perform selected area test, the selected area is the central part of each single crystal particle. When calculating the average value of Ni / Mn element ratio, it is necessary to select 10 particles with the longest diameter less than 1.5μm and greater than 2.5μm, and perform EDS test respectively. Among the 10 Ni / Mn ratios obtained, remove the maximum and minimum values, and then calculate the average value of the remaining 8 values.

[0148] 7. Particle size characterization: Equipment: Wet particle size analyzer. Method: Before testing, the laser intensity should be observed. If it is lower than 70%, the testing department should be notified to clean the lens and water inlet and outlet hoses; after starting to measure the background, perform external ultrasound to dissolve the sample (using the instrument's automatic light alignment and background measurement time to perform external ultrasound to dissolve the sample can reduce the probability of the sample being contaminated by long-term storage); perform external ultrasound for 30 seconds while stirring back and forth; before adding the sample, add 3 drops of sodium hexametaphosphate to the sample pool, stir, and pour all into the sample pool at once; when all the sample is poured in, wait for 10 seconds and click to start the sample test; the laser shading degree should be maintained between 7% and 12%.

[0149] 8. Battery electrode production and conductivity characterization: a. Battery electrode production The obtained positive electrode material was mixed with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 80:10:10, and NMP (N-methylpyrrolidone) was added to make a uniform slurry, which was coated on copper foil, dried in an oven, and cut into circular pole pieces with a diameter of 14 mm after rolling at a pressure of 5 MPa.

[0150] b. Conductivity characterization: Equipment: Electrode resistivity meter.

[0151] Method: Tested using the Kelvin four-wire method: ①Set the test parameters to experimental area = 153.94mm 2 , the pressure before pole piece rolling = 5MPa, the pressure after pole piece rolling = 25MPa, and the holding time = 15s.

[0152] ②Data recording, the resistivity data COV% collected in parallel is less than 5%, otherwise the electrode needs to be re-prepared and re-tested until the requirements are met.

[0153] ③The measured resistivity is recorded as ρ, and the conductivity σ is the reciprocal of the resistivity, σ=1 / ρ.

[0154] 9. Battery production and performance testing a. Preparation of electrochemical performance test samples: Button battery production: ① Ingredients: NCM: SP: 5% PVDF glue = 93: 5: 2 = 9.3 g: 0.5 g: 4.0 g, NMP=9g, stir at high speed to disperse evenly.

[0155] ② Coating and drying: Evenly coat the slurry on 20μm thick aluminum foil with a 210um coater, set the coating length to the maximum length of the coater, cut the back half of the electrode and put it into a 100℃ forced air drying oven to dry for more than 1.5 hours.

[0156] ③Rolling, punching and drying: When rolling, adjust the roller machine to 1 roller gap and roll for 3 times; use a 14mm punching machine to punch holes, weigh, and place in a vacuum drying oven for vacuum drying at 85°C for more than 8 hours.

[0157] ④ Assembly of the button (LIR2016): Positive electrode shell - 2 drops of electrolyte - positive electrode sheet (14mm) - 3 drops of electrolyte - 20μm separator - 2 drops of electrolyte - φ16*1.0mm lithium sheet - 150μm nickel foam - negative electrode shell (dried at 50℃). After the battery is assembled, seal it and take it out of the glove box for testing.

[0158] b. Power-off test: After standing for 12 hours, perform the battery test according to the following system: 0.1C charge and 0.1C discharge for 2 weeks (first effect), constant voltage cut-off current 0.005C; 0.5C charge and 0.5C discharge for 1 week (rate), constant voltage cut-off current 0.05C; 0.5C charge and 1C discharge for 1 week (rate), constant voltage cut-off current 0.05C; 0.5C charge and 2C discharge for 1 week (rate), constant voltage cut-off current 0.05C; 0.5C charge and 1C discharge for 50 cycles, constant voltage cut-off current 0.05C.

[0159] The corresponding test results of the positive electrode materials of Examples 1-15 and Comparative Examples 1-3 are shown in Tables 1 and 2 below.

[0160] Table 1 Table 2 like Figure 3 The SEM image of the oxide precursor prepared in Example 1 is shown in FIG. Figure 3 It can be seen that the particles of the oxide precursor have a certain crystal structure, a large particle size, and are evenly dispersed.

[0161] like Figure 4The SEM image of the positive electrode material prepared in Example 1 is shown in FIG. Figure 4 It can be seen that Example 1 can form single crystal particles with good dispersion, and the gaps between large particles are evenly dispersed with microparticles with smaller particle sizes. Moreover, different regions in the SEM image contain microparticles, and the number of microparticles in different regions is close. In addition, the number of small particles with a particle size of less than 2 microns accounts for a large proportion.

[0162] Further integration Figure 5 As shown, it is the particle size distribution curve of the positive electrode material in Example 1. Figure 5 It can be seen that the peak value (about 2 μm) of the particle size distribution curve of the positive electrode material of Example 1 is asymmetric on both sides, and the area on the left side of the peak value is larger than the area on the right side of the peak value, indicating that the number of particles on the left side of the peak value is greater than the number of particles on the right side. Specifically, the proportion of small particles with a particle size less than 2 μm (including microparticles with a particle size of less than 1 μm) is greater than that of large particles with a particle size greater than 2 μm, and the distribution of large and small particles is wider, which is conducive to further improving the compaction density and conductivity of the positive electrode material while reducing impedance.

[0163] It can be seen from Table 1 and Table 2 that the positive electrode materials prepared in Examples 1-15 have a particle size of less than 1 μm, and the proportion of microparticles is in the range of 8% to 20%. The appropriate amount of microparticles is conducive to improving the compaction density of the positive electrode materials, and the compaction density is greater than 3 g / cm 3, so that the prepared battery can obtain a higher energy density, and the discharge specific capacity of 2.8V~4.35V at 0.1C is greater than 175mAh / g, and the discharge specific capacity of the battery prepared by the positive electrode material of Example 13 is as high as 206.6mAh / g. Secondly, the presence of microparticles can reduce the average particle size of the particles, which is beneficial to shorten the transmission path of lithium ions during charging and discharging, improve the charge transfer effect, and improve the electrode conductivity. The electrode conductivity T at 25MPa is greater than 0.025S / cm, and the positive electrode material of Example 5 has a electrode conductivity of up to 0.0796S / cm. The higher the electrode conductivity, the better the conductivity of the positive electrode material, which effectively reduces the resistance and power consumption of the prepared battery and improves the efficiency of energy transmission. At the same time, the higher the conductivity of the positive electrode material, the more active sites there are in the material. Too many active sites will lead to a large number of side reactions. For this reason, in Examples 1-15, the proportion of microparticles R is limited to 8%-20%, so that the positive electrode material has the advantages of high compaction density and high material activity at the same time, and solves the problems faced by existing positive electrode materials such as uncontrollable number of microparticles leading to increased surface side reactions and increased gas production, thereby improving safety and cycle performance. In addition, a proper amount of microparticles are dispersed in the gaps between large particles. On the one hand, they can provide good support and reduce the risk of particle breakage of large particles during the rolling process of the pole piece, so as to improve the cycle performance of the battery. On the other hand, the microparticles can also act as a buffer in the positive electrode material to disperse stress and inhibit the volume change of the material caused by high conductivity during the charge and discharge process, thereby increasing the structural stability and cycle performance of the positive electrode material. The batteries prepared from the positive electrode materials of Examples 1-15 all have good cycle performance, among which the 50-week cycle retention rate is greater than 95%. In Examples 1-15, by changing different process parameters, the proportion of microparticles in the positive electrode material can be adjusted to optimize the pole sheet conductivity of the positive electrode material and the capacity and cycle performance of the prepared battery.

[0164] Among them, compared with Example 1, the atomization intensity is reduced in Example 2, so that the particle size of the primary particles of the oxide precursor is increased, the reaction activity is weakened, and the distribution of the single crystal particles is widened, thereby increasing the number of microparticles in the positive electrode material and the compaction density of the powder. The discharge specific capacity of the battery is increased to 177.4mAh / g, the first coulomb efficiency is increased to 87.43%, and the electrode conductivity is increased to 0.0621S / cm.

[0165] Compared with Example 1, the pyrolysis temperature is lowered in Example 3, which can reduce the primary particle size of the generated oxide precursor and increase the reaction activity, which is beneficial to the growth of single crystal particles, thereby reducing the proportion of microparticles and reducing the compaction density of the powder, while also reducing the conductivity of the electrode.

[0166] Compared with Example 1, in Example 4, the gas crushing strength during the precursor crushing process is improved, the D50 of the oxide precursor is reduced, the reaction activity is enhanced, which is beneficial to the growth of single crystal particles of the positive electrode material, and the number of microparticles is reduced. Therefore, the compaction density of the powder and the conductivity of the electrode are reduced accordingly.

[0167] Compared with Example 1, in Example 5, the sintering temperature of the fourth sintering stage (high-temperature sintering stage) is increased, the primary particle size of the positive electrode material is increased, and the content of microparticles is increased after the matrix is ​​crushed, which can significantly improve the conductivity of the electrode sheet and the capacity and efficiency of the battery.

[0168] Compared with Example 1, in Example 6, the sintering temperature of the fourth sintering stage (high-temperature sintering stage) is lowered, the primary particle size of the positive electrode material is reduced, and the content of microparticles after crushing is reduced; in addition, the grinding time is reduced, the proportion of large particles increases, the proportion of microparticles decreases, and the conductivity decreases.

[0169] Compared with Example 1, in Example 7, the coated Al2O3 is changed to coated 1000ppm WO3, and the coating amounts of NaOH and KOH are increased to 1000ppm. The coated material is more active and has a larger mass of coated active material, which is beneficial to improving the conductivity of the electrode.

[0170] Compared with Example 1, Examples 8 and 9 changed the lithium source and sintering atmosphere in the primary sintering process, the air atmosphere and lithium carbonate, which are beneficial to the growth of single crystal particles of the positive electrode material, and the proportion of the number of microparticles is reduced. The more lithium carbonate there is, the lower the content of microparticles.

[0171] Compared with Example 1, in Example 10, the gas flow rate and furnace pressure during the primary sintering process are increased, so that the material has more contact with oxygen during the thermal reaction, which is helpful for growing large-grained single crystal materials and reducing the proportion of microparticles.

[0172] Compared with Example 8, Examples 11, 12, 13, and 15 adjust the proportions of the metal elements in the oxide precursor, and can also obtain positive electrode materials with a particle content in the range of 8% to 20%. The electrode conductivity T at 25MPa is greater than 0.033S / cm. At the same time, with the increase of nickel ions, the discharge specific capacity of the battery increases, and is significantly higher than that of the ternary positive electrode material of the 5 series.

[0173] Compared with Example 1, Example 14 uses a mixture of oxide precursors and hydroxide precursors, which allows a larger diffusion width when sintering with lithium salts, and the proportion of microparticles is greatly increased. At the same time, by extending the insulation time in a single sintering process and increasing the oxygen flow rate and furnace pressure, the proportion of microparticles can be controlled within the range of 8% to 20%, thereby optimizing the electrode conductivity and primary effect of the positive electrode material.

[0174] Compared with Example 1, the value of R1 / R2 in Example 12 is larger, indicating that the distribution uniformity of particles below 1 μm in Example 12 is weaker than that in Example 1, resulting in a decrease in the first efficiency and cycle performance of the positive electrode material.

[0175] Compared with Example 1, the value of |R1-R2| in Example 14 is larger, indicating that the distribution uniformity of particles below 1 μm in Example 14 is weaker than that in Example 1, resulting in a decrease in the cycle performance of the positive electrode material.

[0176] However, the proportion of the number of microparticles in the positive electrode materials prepared in Comparative Examples 1-3 is not within the range of 8% to 20%, the number of microparticles is small, the transmission path of lithium ions during charging and discharging is long, the charge transfer efficiency is reduced, and the conductivity of the pole piece is low. Among them, in Comparative Example 1, the grinding air pressure and the frequency of the grading wheel are increased during the crushing process of the positive electrode material matrix, the degree of particle crushing is aggravated, the proportion of the number of microparticles exceeds 20%, the number of microparticles increases, the conductivity of the pole piece is only 0.0212S / cm, and a large number of microparticles aggravate the occurrence of side reactions, and the cycle performance of the prepared battery is reduced. Comparative Example 2 has a low temperature during the first sintering, forming polycrystalline particles, which is not a single crystal positive electrode material. The number of polycrystalline material microparticles is small, the compaction is low, and the positive electrode particles are not fully grown, and the electrochemical performance is affected. Comparative Example 3 uses a hydroxide precursor prepared by coprecipitation. Due to its low crystallinity, it has a narrow diffusion width when reacting with lithium salts. The proportion of microparticles is reduced in the process of forming a single crystal positive electrode material, and the compaction density and tap density are low, and the conductivity performance is also reduced accordingly.

[0177] Therefore, the cathode material prepared by the method of Examples 1-15 of the present application satisfies T>0.025S / cm at 25MPa for the electrode conductivity T. The higher electrode conductivity enables the cathode material to have good electrical conductivity, effectively reducing the resistance and power consumption of the prepared battery, and improving the efficiency of energy transmission. In addition, the proportion of microparticles in the cathode material of Examples 1-15 is in the range of 8%-20%, so that the cathode material has the advantages of high compaction density and high material activity, and solves the problems faced by the cathode material, such as the uncontrollable number of microparticles leading to increased surface side reactions and increased gas production, thereby improving safety and cycle performance.

[0178] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.

Claims

1. A positive electrode material, characterized in that: In the image under the scanning electron microscope at a magnification of 3k, the number of particles less than 1 μm in the positive electrode material accounts for R: 8%≤R≤20%; and under the condition of 25 MPa, the electrode conductivity T of the positive electrode material satisfies: T>0.025S / cm.

2. The positive electrode material according to claim 1, characterized in that Under a scanning electron microscope at a magnification of 3k, the positive electrode material has a first region and a second region, wherein the number of particles below 1 μm in the first region accounts for R1, and the number of particles below 1 μm in the second region accounts for R2, wherein |R1-R2|≤9% and / or 0.5≤R1 / R2≤2.

3. The positive electrode material according to claim 1, characterized in that The two sides of the peak of the particle size distribution curve of the positive electrode material are asymmetric, and the area on the left side of the peak is larger than the area on the right side of the peak.

4. The positive electrode material according to claim 1, characterized in that The positive electrode material is a single crystal positive electrode material, and the average particle size of a single particle in the positive electrode material is 1 μm to 4 μm.

5. The positive electrode material according to claim 1, characterized in that The general formula of the positive electrode material is as follows: Li a Ni b Co c Q d M (1-b-c-d )N e O2, wherein the Q element is selected from at least one of Mn and Al, the M element is selected from at least one of Zr, Ti, Al, Mg and Y, the N element is selected from at least one of Zr, Ti, Al, Co, Mg, W, Ce, Y, K and Na, 0.95≤a≤1.2, 0<b≤1, 0≤c≤1, 0<d≤1, b+c+d+e≤1, 0≤e<1.

6. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following characteristics: (1) The median particle size D50 of the positive electrode material is 2.5 μm to 5 μm, D10 is 1 μm to 2.5 μm, D90 is 6 μm to 10 μm, and 1.0≤(D90-D10) / D50≤1.5; (2) The specific surface area of ​​the positive electrode material is 0.5 m 2 / g~1.4m 2 / g; (3) The compaction density of the positive electrode material is greater than 3.0 g / cm 3 ; (4) The tap density of the positive electrode material is greater than 1.5 g / cc; (5) The bulk density of the positive electrode material is greater than 0.5 g / cm 3 ; (6) The discharge specific capacity of the positive electrode material at 2.8V~4.35V at 0.1C is greater than 175mAh / g.

7. A method for preparing a positive electrode material, characterized in that: The following steps are involved: Mixing the oxide precursor with a lithium source and a dopant and sintering the mixture to obtain a positive electrode material matrix; and The positive electrode material matrix is ​​crushed and coated with a coating agent to obtain the positive electrode material, wherein in an image under a scanning electron microscope at a magnification of 3k, the number of particles less than 1 μm in the positive electrode material accounts for R: 8%≤R≤20%; and under 25 MPa conditions, the electrode sheet conductivity T of the positive electrode material satisfies: T>0.025S / cm.

8. The method for preparing the positive electrode material according to claim 7, characterized in that: Before mixing the oxide precursor with the lithium source and the dopant and sintering, the method further includes atomizing and pyrolyzing the metal mixed solution to obtain the oxide precursor. The preparation method also satisfies at least one of the following characteristics: (1) In the step of atomizing and pyrolyzing the metal mixed solution to obtain the oxide precursor, the total metal concentration in the solution is controlled to be in the range of 2 mol / L to 8 mol / L; (2) In the step of atomizing and pyrolyzing the metal mixed solution to obtain the oxide precursor, the feed flow rate is controlled to be 0.5 m³ / h~5 m³ / h; (3) In the step of atomizing and pyrolyzing the metal mixed solution to obtain the oxide precursor, the atomizing air flow rate is controlled to be 50m³ / h~300m³ / h, and the atomizing pressure is controlled to be 100kPa~700kPa; (4) In the step of atomizing and pyrolyzing the metal mixed solution to obtain the oxide precursor, the pyrolysis temperature is controlled to be 400° C. to 1200° C.; (5) The sintering includes a first sintering stage, a second sintering stage, a third sintering stage and a fourth sintering stage, wherein the sintering temperature of the first sintering stage is 300°C to 600°C and the time is 3h to 5h; the sintering temperature of the second sintering stage is 700°C to 1000°C and the time is 4h to 12h; the sintering temperature of the third sintering stage is 500°C to 700°C and the time is 2h to 6h; the sintering temperature of the fourth sintering stage is 700°C to 1000°C and the time is 1h to 3h; (6) The doping element M in the dopant is selected from at least one of Zr, Ti, Al, Mg and Y; (7) The coating element N in the coating agent is selected from at least one of Zr, Ti, Al, Co, Mg, W, Ce, Y, K and Na.

9. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, characterized in that: The positive electrode active material layer includes the positive electrode material according to any one of claims 1 to 6 or a positive electrode material prepared by the method for preparing a positive electrode material according to claim 7 or 8.

10. A secondary battery, characterized in that: The invention comprises the positive electrode material according to any one of claims 1 to 6 or the positive electrode material prepared by the method for preparing the positive electrode material according to claim 7 or 8.

Citation Information

Patent Citations

  • Positive electrode active material, positive electrode plate, electrochemical energy storage device and new energy automobile

    CN112909238A

  • Positive electrode active material, preparation method thereof and battery

    CN116454253A

  • Positive electrode material, preparation method thereof and battery

    CN117293308A

  • Ternary single-crystal positive electrode material and preparation method and application thereof

    CN117673320A